2019
DOI: 10.1016/j.hpb.2018.10.007
|View full text |Cite
|
Sign up to set email alerts
|

18F-FDG PET/CT predicts microvascular invasion and early recurrence after liver resection for hepatocellular carcinoma

Abstract: Background: This study assessed the prognostic value of 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET)/computed tomography (CT) in the prediction of MVI and early recurrence following resection.Method: This prospective study (ClinicalTrials.gov ID: NCT02145013) included 78 consecutive HCC patients who underwent 18F-FDG PET/CT before curative-intent resection from 2014 to 2017. Prognostic factors available before surgery for predicting MVI and early recurrence (2 years) were identified by u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 51 publications
1
35
0
Order By: Relevance
“…( 22 ) High‐grade [ 18 F]FDG avidity may not only signal a change in metabolome but could also identify a more aggressive and invasive phenotype with a higher risk of microvascular invasion and metastatic disease. ( 8,9 ) For example, Kwee et al correlated high tumor [ 18 F]‐fluorocholine uptake with specific gene signatures and increased mortality. ( 23 ) Although prior studies have shown that PET‐CT positivity is associated with microvascular invasion and recurrence risk after surgical resection ( 9 ) and liver transplantation, ( 12 ) we did not have the sample size of patients in these subgroups to corroborate this finding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…( 22 ) High‐grade [ 18 F]FDG avidity may not only signal a change in metabolome but could also identify a more aggressive and invasive phenotype with a higher risk of microvascular invasion and metastatic disease. ( 8,9 ) For example, Kwee et al correlated high tumor [ 18 F]‐fluorocholine uptake with specific gene signatures and increased mortality. ( 23 ) Although prior studies have shown that PET‐CT positivity is associated with microvascular invasion and recurrence risk after surgical resection ( 9 ) and liver transplantation, ( 12 ) we did not have the sample size of patients in these subgroups to corroborate this finding.…”
Section: Discussionmentioning
confidence: 99%
“…( 6 ) However, data from Europe and Asia are beginning to suggest that PET‐CT may have a role in the staging and management of HCC including early detection of disease recurrence following resection as well as identification of occult intrahepatic and extrahepatic metastasis or vascular invasion. ( 7‐13 )…”
mentioning
confidence: 99%
“…Hyun et al reported that higher TLR (≥2) was significantly associated with death in patients underwent curative treatments including resection, liver transplantation, and radiofrequency ablation [24]. Lim et al showed that visual positivity of 18 F-FDG-PET was an independent predictor for early recurrence after liver resection in their prospective observation study [25]. In the present study, visual qualitative analysis was used to evaluate 18 F-FDG uptake because in clinical practice, visual analysis is easier than quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%
“…The 18 F-FDG uptake of HCC is variable; K19-positive HCC is associated with high 18 F-FDG uptake. In addition, high 18 F-FDG uptake in HCC has been associated with poor differentiation, microvascular invasion, advanced tumor stage, and a poor outcome after surgical resection or transplantation [97][98][99]. In an in vitro study, the K19-positive tumor cell subpopulation displayed higher 18 F-FDG uptake than the K19-negative subpopulation, and K19 expression was found to increase 18 F-FDG uptake through TGF-β/Smad signaling and the subsequent upregulation of the glucose transporter GLUT1 [83].…”
Section: High Uptake Of 18 F-fdgmentioning
confidence: 99%